Corporate social responsibility in India : cases and developments after the legal mandate - Mitra, Nayan; Schmidpeter, René (Springer, 2017)
This book provides a comprehensive overview of Corporate Social Responsibility (CSR) in Indian corporations following the 2013 legal mandate on corporate spending of profits for CSR. Bringing together authors hailing from diverse walks of life, the book pursues a 'hands-on' approach, with real-world case studies and examples that help the reader feel the dynamic pulse of India immediately after the ratification of the CSR mandate in the Companies Act, 2013. The Act is expected to affect over 16,300 companies with an estimated flow of approximately 200 billion Indian rupees into the economy every year, thus shaking the foundations of business and society and impacting the country at multiple stakeholder levels. As a result, India is likely to become the birthplace of social, economic, and environmental transformation through financial investments in CSR! In order to insightfully reflect on this transition, this book has been divided into three parts. The first part presents the CSR mandate and its implications, while the second focuses on its implementation and the third part provides a view on the way forward. The book helps to reveal the various layers of CSR in an emerging economy like India and is expected to spark debate, discussion and research among policy-makers, consultants, academics, practitioners and other stakeholders the world over, which will further expand its contribution to CSR literature and open up new vistas in CSR research. "This is indeed a first of its kind book and marks a watershed in the journey of CSR. It is an extremely important contribution to the body of knowledge in the area of CSR and Corporate Governance in emerging economies that is driven by a completely different set of challenges, opportunities and requirements from that of developed economies." Dr. Bhaskar Chatterjee, Director General & CEO, Indian Institute of Corporate Affairs.
Keywords: Social responsibility of business -- India.; Sustainable development -- India.; Industrial management -- Environmental aspects.; Corporate governance -- India.; Management -- Social aspects.; Globalization.; elektronické knihy; electronic books